KEPUASAN DAN MOTIVASI TENAGA MEDIS : STUDI KASUS TERHADAP PENDAPATAN, KOMPENSASI DAN LINGKUNGAN KERJA PADA RSUD Dr. SOEDIRMAN KABUPATEN KEBUMEN - Iwan Danardono; Firman Pribadi (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Quality of services in hospital is determined by the performance of medical workers. It is a human resources that mostly determine the hospital performance. Manager should pay attention to the problem of job satisfaction and the factors that affect the work motivation of medical workers. Aim of the study to examinee the relationship between health worker incomes and work environment to their satisfactionand motivation. Method: This study descriptive qualitative case study design with objects are medical staff. Questionare based on Immpact Toolkit ”Health Worker Incentives Survey (HWIS)”from University of Abeerden. Results and Discussion: Distributionof incentivesbetweentypes ofmedical workersis quitevaried,this causesdissatisfaction.57% of respondents believe that thenew buildingis nowa greatplace.85% of respondents are notinterested toleave the professionnowas a medical staff. 15% of respondentsundecidedwhether toleavethe professionnowornot. 100% of respondentsclaimedno onewould resign from RSUD dr. Soedirman.62% of respondentsexpressed satisfaction with thehighcategory, 27% of respondent swerenot satisfied because the working conditions. Some 11% of respondentsexpressedsatisfactionwith theworkin low category. Background respondents withlow satisfaction is general practitioner ordentist. Conclusions: The amount ofrevenuesandservicesreceivedfluctuateanddifferfrom individual toindividual. There is adisparitybetweenmedical personnelandcivil servants PTT, and betweentypes ofmedical personnelin terms ofthe amount ofrevenueandservicesreceived, itcauses themajority ofrespondentshave low incomeschoose the level ofjob satisfactionat the level ofmedium and low, but caused nodesireto movethe workplace.there arerespondentswhocomplained ofpoorworking conditionsandthis led totheir job satisfactionin the low category.